Subretinal Pigment Epithelial Deposition of Drusen Components Including Hydroxyapatite in a Primary Cell Culture Model - Pilgrim, Matthew G.; Lengyel, Imre; Lanzirotti, Antonio; Newville, Matt; Fearn, Sarah; Emri, Eszter; Knowles, Jonathan C.; Messinger, Jeffrey D.; Read, Russell W.; Guidry, Clyde; Curcio, Christine A. (Investigative ophthalmology & visual science, 2017)
Extracellular deposits containing hydroxyapatite, lipids, proteins, and trace metals that form between the basal lamina of the RPE and the inner collagenous layer of Bruch's membrane are hallmarks of early AMD. We examined whether cultured RPE cells could produce extracellular deposits containing all of these molecular components. Retinal pigment epithelium cells isolated from freshly enucleated porcine eyes were cultured on Transwell membranes for up to 6 months. Deposit composition and structure were characterized using light, fluorescence, and electron microscopy; synchrotron x-ray diffraction and x-ray fluorescence; secondary ion mass spectroscopy; and immunohistochemistry. Apparently functional primary RPE cells, when cultured on 10-μm-thick inserts with 0.4-μm-diameter pores, can produce sub-RPE deposits that contain hydroxyapatite, lipids, proteins, and trace elements, without outer segment supplementation, by 12 weeks. The data suggest that sub-RPE deposit formation is initiated, and probably regulated, by the RPE, as well as the loss of permeability of the Bruch's membrane and choriocapillaris complex associated with age and early AMD. This cell culture model of early AMD lesions provides a novel system for testing new therapeutic interventions against sub-RPE deposit formation, an event occurring well in advance of the onset of vision loss.